2003
DOI: 10.1186/cc2386
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction The present study was conducted to assess the value of serum concentration of lipopolysaccharide-binding protein (LBP) in patients with systemic inflammatory response syndrome (SIRS), sepsis and septic shock with respect to its ability to differentiate between infectious and noninfectious etiologies in SIRS and to predict prognosis. Methods This prospective cohort study was conducted in a multidisciplinary intensive care unit. Sixty-eight patients, admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
(27 reference statements)
7
35
0
Order By: Relevance
“…As noted previously, about 1/6 of the sequences identified in this study correspond to genes that were previously reported to be affected by EHI (Sonna et al 2004). Furthermore, of the 12 sequences for which the expression response to temperature was affected by clinical diagnosis in this study, at least three correspond to proteins that have been found by others to display different levels of expression in serum obtained from patients with sepsis vs. noninfectious SIRS:interleukin 8 (Rodriguez-Gaspar et al 2001), lipopolysaccharide binding protein (Prucha et al 2003), and HSP 70 (Adib-Conquy and Cavaillon 2007). Finally, housekeeping genes reported to show stable expression after exertional hyperthermia in vivo in a prior work (Sonna et al 2004) also showed stable expression with respect to temperature and clinical diagnosis in this study.…”
Section: Discussionsupporting
confidence: 75%
“…As noted previously, about 1/6 of the sequences identified in this study correspond to genes that were previously reported to be affected by EHI (Sonna et al 2004). Furthermore, of the 12 sequences for which the expression response to temperature was affected by clinical diagnosis in this study, at least three correspond to proteins that have been found by others to display different levels of expression in serum obtained from patients with sepsis vs. noninfectious SIRS:interleukin 8 (Rodriguez-Gaspar et al 2001), lipopolysaccharide binding protein (Prucha et al 2003), and HSP 70 (Adib-Conquy and Cavaillon 2007). Finally, housekeeping genes reported to show stable expression after exertional hyperthermia in vivo in a prior work (Sonna et al 2004) also showed stable expression with respect to temperature and clinical diagnosis in this study.…”
Section: Discussionsupporting
confidence: 75%
“…They measured LBP plasma levels in 253 patients with severe sepsis and/or septic shock and reported mean LBP levels in the lower range of those not only in our series but also in other recent reports [13], [22], [29]. They found that LBP levels were less elevated in non-survivors than survivors.…”
Section: Discussionsupporting
confidence: 71%
“…Prucha et al [13] assessed LBP levels at study entry and at 3- to 5-day intervals for 30 days or until death in a mixed population of 68 patients with systemic inflammatory response, sepsis or septic shock. However, they did not find significant differences in LBP levels between patients with systemic inflammatory response and sepsis or between survivors and non-survivors, since only 9 patients had severe sepsis and/or septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows differentiating infectious and noninfectious inflammation, local or systemic infection, as well as predicting the severity of the course of sepsis and its outcomes [16].…”
Section: Results and Descussionmentioning
confidence: 99%